Ciclos de Goodwin e o paradigma BOPC: um modelo macrodinâmico de crescimento e flutuações - Marwil Jhonatan Dávila Fernandez (2015)
This dissertation presents a non-linear macrodynamic model to study the relation between the functional distribution of income, technological progress and economic growth. In the short-term the interaction between the productivity regime, the demand regime and the distributive conflict generate cyclical paths a la Goodwin. In the long-term output growth rate is limited by the balance of payments a la Thirlwall in which the elasticities of foreign trade are modeled as a function of the complex relation between the wage-share and the innovation capabilities of the economy.